Lung Cancer Mortality in the Swiss Working Population: The Effect of Occupational and Non-Occupational Factors. Issue 12 (December 2021) - Bovio, Nicolas; Wild, Pascal; Guseva Canu, Irina
Abstract : Objective: To assess the effect of occupational exposures on lung cancer mortality in Switzerland after adjustment for non-occupational lung carcinogens. Methods: Using data on 4, 351, 383 Swiss residents, we used negative binomial regression to assess the effect occupation on lung cancer mortality between 1990 and 2014, accounting for socio-demographic factors, predicted probabilities of smoking and measured environmental radon exposure. Results: After adjustment, male machine operators and workers in mining, stone working and building materials manufacturing showed the highest risk. Women working in electrical engineering, electronics, watchmaking, vehicle construction and toolmaking, and transport occupations also remained at high risk. Radon exposure had no effect on lung cancer mortality, while smoking demonstrated a significant effect in both sexes. Conclusions: The results suggest the presence of occupational exposures to lung carcinogens in addition to non-occupational factors. Abstract : Supplemental Digital Content is available in the text